2013
DOI: 10.1111/wbm.12008
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control of weedy rice in precise hill‐direct‐seeded rice in South China

Abstract: Precise hill‐direct‐seeded rice, which is both cost‐ and labor‐saving, is based on the direct seeding of rice by using a precision rice hill‐drop drilling machine. Weedy rice (Oryza sativa f. spontanea), also known as “red rice”, is a major weed in precise hill‐direct‐seeded rice, causing an ≤80% yield loss and a reduction in grain quality. The aim of this study was to evaluate the control efficiency of weedy rice by pretilachlor (a pre‐emergence herbicide) and fenclorim (a safener) and their safety for precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
2
13
1
Order By: Relevance
“…Safeners are used to enhance herbicide tolerance in selected monocot crops without affecting herbicidal susceptibility of the target weed species (Davies and Caseley, 1999;Shen et al, 2013). In a recent study in China, the pretilachlor herbicide applied at 1350 g ha -1 reduced rice fresh weight by only 7% (Shen et al, 2013). However, in our study, the maximum rate of pretilachlor was only 900 g ha -1…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…Safeners are used to enhance herbicide tolerance in selected monocot crops without affecting herbicidal susceptibility of the target weed species (Davies and Caseley, 1999;Shen et al, 2013). In a recent study in China, the pretilachlor herbicide applied at 1350 g ha -1 reduced rice fresh weight by only 7% (Shen et al, 2013). However, in our study, the maximum rate of pretilachlor was only 900 g ha -1…”
Section: Resultscontrasting
confidence: 66%
“…As the pretilachlor used in our study had a safener in it, no phytotoxic effects were observed. Safeners are used to enhance herbicide tolerance in selected monocot crops without affecting herbicidal susceptibility of the target weed species (Davies and Caseley, 1999;Shen et al, 2013). In a recent study in China, the pretilachlor herbicide applied at 1350 g ha -1 reduced rice fresh weight by only 7% (Shen et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism of action of most plants aqueous extracts is still unclear but many reports have mentioned phytotoxicity of used plant combinations in their individual capacity. A possible mechanism may involve a decreased activity of some enzymes like proteases, ureases and phosphorelases, a decline in chlorophyll content and photosynthesis, a greater cell membrane permeability and lipid metabolism (Shen et al, 2013).…”
Section: Maize Growth Indicesmentioning
confidence: 99%
“…Consequently, favoring crop growth indices like leaf area index, leaf area duration, dry matter accumulation and crop growth rate through lessening the competition for available resources and improving yield components in maize, cob length, number of grains per cob, 1000 grain weight thus, resulted in higher stalk, and economic and biological yield (Catherine et al, 2003;Shen et al, 2013).…”
Section: Maize Growth Indicesmentioning
confidence: 99%